Mother-fetus immune cross-talk coordinates "extrinsic"/"intrinsic" embryo gene expression noise and growth stability - Babochkina, Tatyana Ivanovna; Gerlinskaya, Ludmila A.; Anisimova, Margarita V.; Kontsevaya, Galina V.; Feofanova, Nataly A.; Stanova, Aliya Konstantinovna; Moshkin, Mikhail P.; Moshkin, Yuri M. (International journal of molecular sciences)
Developmental instability (DI) is thought to be inversely related to a capacity of an organism to buffer its development against random genetic and environmental perturbations. DI is represented by a trait's inter- and intra-individual variabilities. The inter-individual variability (inversely referred to as canalization) indicates the capability of organisms to reproduce a trait from individual to individual. The intra-individual variability reflects an organism's capability to stabilize a trait internally under the same conditions, and, for symmetric traits, it is expressed as fluctuating asymmetry (FA). When representing a trait as a random variable conditioned on environmental fluctuations, it is clear that, in statistical terms, the DI partitions into extrinsic (canalization) and intrinsic (FA) components of a trait's variance/noise. We established a simple statistical framework to dissect both parts of a symmetric trait variance/noise using a PCA (principal component analysis) projection of the left/right measurements on eigenvectors followed by GAMLSS (generalized additive models for location scale and shape) modeling of eigenvalues. The first eigenvalue represents extrinsic and the second-intrinsic DI components. We applied this framework to investigate the impact of mother-fetus major histocompatibility complex (MHC)-mediated immune cross-talk on gene expression noise and developmental stability. We showed that intrinsic gene noise for the entire transcriptional landscape could be estimated from a small subset of randomly selected genes. Using a diagnostic set of genes, we found that allogeneic MHC combinations tended to decrease extrinsic and intrinsic gene noise in C57BL/6J embryos developing in the surrogate NOD-SCID and BALB/c mothers. The intrinsic gene noise was negatively correlated with growth (embryonic mass) and the levels of placental growth factor (PLGF), but not vascular endothelial growth factor (VEGF). However, it was positively associated with phenotypic growth instability and noise in PLGF. In mammals, the mother-fetus MHC interaction plays a significant role in development, contributing to the fitness of the offspring. Our results demonstrate that a positive impact of distant MHC combinations on embryonic growth could be mediated by the reduction of intrinsic gene noise followed by the developmental stabilization of growth.